Up Close : A Lifetime Observing and Photographing Desert Animals - Olin, George (Book collections on Project MUSE., 2000)
In this memoir, Olin combines personal and natural history to recount his long fascination with animals. In addition to painting a vivid picture of his nomadic life, he describes the methods he devised to observe desert creatures and build their trust--and the lessons they taught him in return.